Weed Hosts of Root-Knot Nematodes Common to Florida - Jimmy R. Rich; Janete Brito; Jason Ferrell; Ramandeep Kaur (EDIS, 2010)
ENY-060, a 7-page illustrated fact sheet by Jim Rich, Janete Brito, Jay Ferrell, and Ramandeep Kaur, discusses the importance of weeds as nematode hosts, and how knowledge of symptomatic weed hosts can monitor fields for nematodes. Includes a table of selected Florida weeds occurring as hosts of root-knot nematodes. Published by the UF Department of Entomology and Nematology, April 2010.